The architecture of school governance: Rebuilding democratic legitimacy within an academized system. (January 2022) - Allen, Andrew; Gann, Nigel
Successive governments, in embracing a neoliberalist ideology of decentralization and privatization, have radically reformed the nature of community-based, comprehensive state education. The transition from 'government to governance' (Rhodes, 1997) combined with the ideology of academization (DfE, 2010a) has created a democratic deficit 1 (Corbett, 1977). Academies are placed outside of local elected scrutiny or community-based accountability systems and governance legitimacy is in crisis (Glatter, 2013). This article explores the problematization of academized governance (Allen and Gann, 2017) with respect to the democratic deficit and the consequential lack of stakeholder engagement – argued as unethical within a democratic society and a system that frequently leads to failings of accountability (Wilkins, 2016). Utilizing the conceptual lens of Empowered Participatory Governance (EPG) (Fung and Wright, 2003), the authors seek to present a new architecture of governance that seeks to restore democratic legitimacy. Democratic governance innovations, the micro-governance network (Allen, 2017) and a refreshed local education board (Gann, 2021) provide a new architecture for a post new governance environment and, in so doing, a counter-narrative to the rhetoric of academization.